Development of bismuth sodium borate glasses for radiation shielding material. (2021) - Cheewasukhanont, W.; Limkitjaroenporn, P.; Kaewjaeng, S.; Chaiphaksa, W.; Hongtong, W.; Kaewkhao, J.
Abstract: Glass samples of the bismuth sodium borate (where x = 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 mol%) have been prepared in laboratory by melt quenching technique. The radiation shielding properties including the mass attenuation coefficient, the effective atomic number, the effective electron density and the half value layer (HVL) of glass samples have been measured by using the gamma ray from radioactive source Ba-133, Na-22, Cs-137 and Co-60 at the energies 356, 511, 662, 1173 and 1332 keV for these experiment and those were compared with theoretical approach by WinXCom program. The results found that, the mass attenuation coefficient, effective atomic number, and effective electron density were increased with the increase of Bi2 O3 concentrations, and those values were decreased with the increasing of gamma-ray energies. The glasses in this work showed good radiation shielding properties by providing less the HVL than some standard shielding materials at 662 keV of gamma ray